Megadose Bone Marrow and Regulatory T cells for the Induction of Immune Tolerance in Non-Human Primates Through Durable Mixed Hematopoietic Chimerism Across MHC-barriers. (July 2018) - Alonso-Guallart, Paula; Duran-Struuck, Raimon; Stern, Jeffrey; Berglund, Erik; Llore, Nathaly; Zitsman, Jonah; Pierre, Genevieve; Kofman, Sigal; Danton, Makenzie; Gokova, Samanta; Lopes, Emily; McMurchy, Alicia; et al.
Abstract : Introduction: ?Mixed hematopoietic chimerism is a promising approach to achieving transplantation tolerance. Transient mixed chimerism (MC) leads to renal allograft tolerance in about 60% of Cynomolgus macaques (CM) when a donor kidney is co-transplanted with MHC-mismatched bone marrow (BMT). These findings are not recapitulated with other solid organs. The addition of regulatory T cells (Tregs) to BMT has promoted long-term MC and skin graft tolerance in mice. We aim to test the effect of high bone marrow dose and Treg administration with the hypothesis that these will enhance the duration and degree of donor MC in the CM model with the ultimate goal of inducing tolerance to any donor organ. Materials and Methods: CM recipients were conditioned with total body irradiation (1.25Gy, days -6, -5), thymic irradiation (7Gy, day -1), ATGAM (days -2, -1, 0), anti-CD40L (days 0, 2, 5, 7, 9, 12) and rapamycin for 30 days (day -2 to 28) and tapered down thereafter. MHC-mismatched bone marrow (BM) was infused either on day 0 (Group A) or 2 (Group B) along with the first dose of polyclonal recipient Tregs. Consecutive Treg doses were given during the following week and on day (+/-) 50 for a total of five doses. Tregs were expanded either with artificial antigen presenting cells (aAPC) and donor PBMCs or CD40L-stimulated B cells. Results: Animals received cell doses detailed in Figure 1. Among all the Treg-treated animals, 5/6 developed high and long-lasting MC (Figure 2). Among those, the animals that received Tregs stimulated with activated B cells achieved full donor chimerism, which in one was associated with biopsy-proven graft-versus-host-disease (GVHD). The Treg recipient that lost chimerism earlier did so in association with substantial CMV viremia, and associated immune activation. Two of 4 controls lost MC early post-BMT. In one control the MC started to decrease at the time of sacrifice due to infection and the fourth control developed full donor chimerism and GVHD. In vitro, Treg treated animals were donor-hyporesponsive while chimeric.? Discussion: Megadose BMT prolonged MC over historical controls that received lower doses of HSC. Prolonged MC was achieved in all the animals that received Tregs except for one with CMV reactivation, and those treated with Tregs generated with activated-B cells had full donor chimerism. In addition, one of the controls achieved full donor chimerism with GVHD. Conclusions: Megadose BMT across MHC barriers prolongs donor MC. MC is further prolonged by administering expanded polyclonal recipient Tregs at the time of BMT. NIH R01 OD017949. S10RR027050. S10OD020056. Figure. No caption available. Figure. No caption available.